Differentiation of acute cholecystitis from chronic cholecystitis: Determination of useful multidetector computed tomography findings. Issue 33 (August 2018) - Yeo, Dong Myung; Jung, Seung Eun
Abstract : Abstract: The purpose of this study was to determine the diagnostic value of multidetector computed tomography (MDCT) imaging findings, to identify the most predictive findings, and to assess diagnostic performance in the diagnosis and differentiation of acute cholecystitis from chronic cholecystitis. In this retrospective study, we enrolled 382 consecutive patients with pathologically proven acute or chronic cholecystitis who underwent computed tomography (CT) within 1 month before surgery. The CT findings were compared and logistic regression analysis was used to identify significant CT findings in predicting acute cholecystitis. Diagnostic performance of each CT finding and of combined findings was also assessed. Statistically significant CT findings distinguishing acute cholecystitis from chronic cholecystitis were increased gallbladder dimension (85.5% vs 50.6%, P < .001), increased wall enhancement (61.8% vs 78.9%, P = .001), increased wall thickness (67.9% vs 31.1%, P < .001), mural striation (64.9% vs 28.3%, P < .001), pericholecystic haziness or fluid (66.4% vs 21.2%, P < .001), increased adjacent hepatic enhancement (80.0% vs 32.4%, P < .001), focal wall defect (9.2% vs 0, P < .001), and pericholecystic abscess (10.7% vs 0, P < .001). Subsequent multivariate logistic regression analysis revealed that increased adjacent hepatic enhancement [ P = .006, odds ratio (OR) = 3.82], increased gallbladder dimension ( P = .027, OR = 3.12), increased wall thickening or mural striation ( P = .019, OR = 2.89), and pericholecystic haziness or fluid ( P = .032, OR = 2.61) were significant predictors of acute cholecystitis. When 2 of these 4 CT findings were observed together, the sensitivity, specificity, and accuracy for the detection of acute cholecystitis were 83.2%, 65.7%, and 71.7%, respectively. When 3 of these 4 CT findings were observed together, the sensitivity, specificity, and accuracy were 56.5%, 84.5%, and 74.9%, respectively. When none of these 4 CT findings were observed, the negative predictive value was 96.4%. Increased adjacent hepatic enhancement, increased gallbladder dimension, increased wall thickening or mural striation, and pericholecystic fat haziness or fluid were the most discriminative MDCT findings for the diagnosis and differentiation of acute cholecystitis from chronic cholecystitis.